Visualisation as a Model. Overview on Communication Techniques in Transport and Urban Planning - Rabino, Giovanni; Masala, Elena (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Information and Communication Technologies (ICT) changed the way planners present and operate with their projects. New visualisation tools have changed the ways projects and plans are presented and disseminated. However, the opportunities given by visualisation are not completely exploited in the professional practice. This is due to several bottlenecks which occur in the daily carrying out of activities. The paper is organised in three sections. The first one explains how visualisation can be an added value to the planning practice if it is organised and designed as a framework of information; conceiving the visualisation as a model, data can be managed and represented in order to provide information at different levels of expertise, allowing city plans to be analysed and understood before their realisation. The second section resumes the changes caused by the introduction of ICT within the daily practice; a comparison between pre-digital and digital approaches highlights current opportunities for implementing the communication values of plans and projects. The third part illustrates some examples of innovative visualisations in the urban and transport planning practice, showing a number of uses of visualisation to fit different purposes. The paper concludes this insight formulating the necessity for integrating the studies on visualisation coming from different disciplines into a scientific method that can be proposed as a guideline in building the images of urban and transport plans. This would be particularly useful for obtaining a more scientific approach in the choices of representation and visualisation of urban aspects.